2020
DOI: 10.1108/jsm-07-2019-0270
|View full text |Cite
|
Sign up to set email alerts
|

Eye for an eye? Frontline service employee reactions to customer incivility

Abstract: Purpose Frontline service employees (FSEs) face high demands of emotional labor when dealing with difficult, and sometimes even uncivil, customer behavior while attempting to deliver service with a smile. The purpose of this study is to investigate whether employees reciprocate uncivil customer behavior. The authors investigate two potential processes – ego threat and perceived interactional justice – and further address boundary conditions of this effect. Design/methodology/approach The data for this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 90 publications
1
36
0
1
Order By: Relevance
“…Researchers assert that stress management programs (e.g., relaxation and mindfulness training) can guard FSEs against customer incivility (Frey-Corders et al 2020 ; Sliter et al 2010 ). Training programs that promote emotion regulation abilities and perspective taking can also help FSEs in understanding the position of customers better and displaying emotions toward them more effectively (Sliter et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers assert that stress management programs (e.g., relaxation and mindfulness training) can guard FSEs against customer incivility (Frey-Corders et al 2020 ; Sliter et al 2010 ). Training programs that promote emotion regulation abilities and perspective taking can also help FSEs in understanding the position of customers better and displaying emotions toward them more effectively (Sliter et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, our mediation analyses failed to consider any potential moderators that strengthened or weakened the effect of interpersonal stressors in the pandemic context. COVID-19 research has shown that FSEs’ emotional intelligence (Frey-Corders et al 2020 ) and resilience (Al-Hawari et al 2020 ) mitigate the deleterious effect of customer incivility. In addition, social capital and network and collaborative knowledge creation have been found to help organizations and individuals effectively respond to the COVID-19 pandemic (Al-Omoush et al 2020 ; Belso-Martínez et al 2020 ; López-Cabarcos et al 2020 ; Xie et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…repayment vs retaliation) and in this paper retaliation is seen as a negative reciprocal act, i.e. an eye for an eye (Schieffelin 1980;Frey-Cordes et al 2020).…”
Section: Reciprocity As Retaliationmentioning
confidence: 99%
“…retaliation, as well as to the related concept of restorative justice have been neglected. Mostly, these constructs have been investigated in isolation and single-sidedly (Frey-Cordes et al 2020;Greer 2015;Grégoire and Fisher 2006;Jung and Yoo 2017;Lee and Kim 2019a). Furthermore, society has predominantly advanced a Westernised and rather mechanistic view of reciprocity (Weiner 1980;Young 2011) and ignored the dynamic nature of an integrated concept of reciprocity (Chen and Chen 2004;Metge 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Second, showing anger breaks the social norm and is particularly unacceptable in Eastern culture, where harmonious relations are extremely valued (Glikson et al, 2019). In such case, employees may feel interactive injustice and get angry at the rude customer (Frey-Cordes et al, 2020;Rupp and Spencer, 2006), resulting in their "negativity reciprocity," that is, returning offensiveness with less effort on work, more incivility and even deliberate undermining (Zhang et al, 2008). Finally, according to the regulatory depletion theory, customer anger as a stressor expends FLEs' cognitive resources, such that they have little mental resources to control their anger and get the job NBRI 12,2 done (Walker et al, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%